Metabarcoding identification of botanical origin of bee-collected pollen samples: comparison of ITS2 reference database performance before and after enrichment with sequences of bee plant species - Ilahi, Wafa (2020)
Mestrdo de dupla diplomação com a High Institute of Biotechnology of Monastir